(1)
f'(x)=1/x-e^(x+a)
f'(1)=1-e^(1+a)=0
1+a=0
a=-1
∴f(x)=lnx-e^(x-1)
f'(x)=1/x-e^(x-1)
無法直接比較大小
畫出1/x和e^(x-1)圖像
![](http://c.hiphotos.baidu.com/zhidao/wh%3D600%2C800/sign=738d3bff74094b36dbc713eb93fc50e1/503d269759ee3d6d17db42eb41166d224f4adef5.jpg)
當(dāng)x∈(0,1)時
f'(x)>0
x=1時
f'(x)=0
當(dāng)x∈(1,+∞)時
f'(x)<0
∴f(x)的增區(qū)間(0,1]
減區(qū)間是(1,+∞)
(2)∵a>=-2
∴e^(x+a)>=e^(x-2)
∴-e^(x+a)<=-e^(x-2)
f(x)=lnx-e∧(x+a)<=lnx-e^(x-2)
即只需證明a=-2時
f(x)<0即可
f'(x)=1/x-e^(x-2)
![](http://h.hiphotos.baidu.com/zhidao/wh%3D600%2C800/sign=fe164e215e6034a829b7b087fb23656c/14ce36d3d539b6005dc0c897eb50352ac65cb780.jpg)
f(x)先增后減
設(shè)f'(x0)=1/x0-e^(x0-2)=0
1/x0=e^(x0-2)①
ln(1/x0)=-lnx0=x0-2
lnx0=2-x0②
∴x=x0時有最大值
f(x0)=lnx0-e^(x0-2)
=2-x0-1/x0
=(-x0^2+2x0-1)/x0
=-(x0-1)^2/x0
∵x0>1
∴-(x0-1)^2/x0<0
∴最大值f(x0)<0
∴當(dāng)a≥-2時,證明fx<0
請及時點擊右下角的【好評】按鈕或者“采納為滿意答案”,